Data subject rights in the era of AI - Rute Silva Gomes (Quaderns IEE, 2025)
The widespread use of AI and its increasing capabilities, as well as the impact of decisions made by AI systems on the lives of natural persons, have prompted discussions on the extent to which existing regulations are well equipped to deal with these systems. In this context, we can ask what is the role of the right of rectification in protecting data subjects from incorrect inferences made by AI systems and to what extent this right could play a key role in protecting data subjects from those inferences. To answer these questions, we propose to examine what rights are granted to data subjects under article 16 of the GDPR; what is the current state of play regarding the application of this right to inferences; to which extent should data subjects have a right to rectify or complete inferences about them made by AI systems; and what are the obligations and good practices that could be implemented to facilitate the exercise of this right in the aforementioned context. We argue the right to rectification may indeed be key to challenging inferences made by AI systems, provided there is a clear and consistent interpretation of its scope and the obligations it entails.